Robots worldwide: the impact of automation on employment and trade - Carbonero, Francesco; Ernst, Ekkehard; Weber, Enzo (Geneva, 2018)
"The impact of robots on employment and trade is a highly discussed topic in the academic and public debates. Particularly, there are concerns that automation may threat jobs in emerging countries given the erosion of the labour cost advantage. We provide evidence on the effects of robots on worldwide employment, including emerging economies. To instrument the use of robots, we introduce an index of technical progress, defined as the ability of robots to carry out different tasks. Robots turn out to have a statistically significant negative impact on worldwide employment. While it is small in developed countries, for emerging economies it amounts to -14% between 2005 and 2014. Furthermore, we assess cross-country effects, finding that robots in developed countries decrease off-shoring just as employment in emerging economies."